Impact of Organizational Values, Compassion, and Well-Being on Industrial Disputes: An Empirical Study - Biswas, Wendrila; Chakraborty, Debarun (Prabandhan: Indian Journal of Management, 2019)
Purpose: The study aimed to enumerate empirically that the phenomenon of the new intricate industrial set up has given rise to complicated, indirect, and impersonal industrial relations which enkindle industrial disputes and entangle entire organizations that need to be unraveled through the manifestations of a culture of mutual understanding and shared feeling. Organizational culture determines the standard of behavior of its employees and guides their words and deeds, thereby mollifying the disagreements and disputes. Design/Methodology: A descriptive cross sectional survey was conducted through a formalized and concealed questionnaire. Multistage sampling was used. Structural equation modeling was used on the proposed conceptual model to conduct confirmatory factor analysis. Findings: The research revealed the major fact that compassion towards employees had a strong positive impact on organizational culture, which also had a crucial as well as positive role on curbing industrial disputes. Research Limitations: The research was conducted in the Indian context with reference to selected manufacturing companies of West Bengal. The outcomes may vary when applied to other sectors of the industry in different states of the country. The research work laid down the base and provided an essence to contemplate and examine further. Managerial Implications: When organizations inculcate value sense within employees, focused on employee well-being as well as lend a hand of support and concern, a feeling of oneness develops, which prevents them from involving in any practice of disorder and unrest and ensures faithfulness and attachment at work.